2015
DOI: 10.2903/j.efsa.2015.4271
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of selenium compounds (E8) as feed additives for all animal species: sodium selenite (coated granulated preparation), based on a dossier submitted by Doxal Italia S.p.A

Abstract: Scientific Opinion on the safety and efficacy of selenium compounds (E8) as feed additives for all animal species: sodium selenite (coated granulated preparation), based on a dossier submitted by Doxal Italia S.p.A. ABSTRACTSelenium is a trace element that is essential for vertebrates and involved in a series of vital metabolic functions. The additive, a coated granulated preparation of sodium selenite, consists of carrier granules to which the active compound, sodium selenite, is fixed using filming agents; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In previous opinions, the FEEDAP Panel assessed the safety for the environment of the inorganic source of sodium selenite when used in animal nutrition up to the maximum authorised content in feed and concluded that not concerns to the environment were expected (EFSA FEEDAP Panel, 2015, 2016a. The additive under assessment, sodium selenate for use in complementary feed for ruminants in the form of ruminal boluses, is intended to be a substitute for other authorised selenium additives and will not further increase the environmental burden of selenium.…”
Section: Safety For the Environmentmentioning
confidence: 99%
“…In previous opinions, the FEEDAP Panel assessed the safety for the environment of the inorganic source of sodium selenite when used in animal nutrition up to the maximum authorised content in feed and concluded that not concerns to the environment were expected (EFSA FEEDAP Panel, 2015, 2016a. The additive under assessment, sodium selenate for use in complementary feed for ruminants in the form of ruminal boluses, is intended to be a substitute for other authorised selenium additives and will not further increase the environmental burden of selenium.…”
Section: Safety For the Environmentmentioning
confidence: 99%
“…The FEEDAP Panel considered also a recently published book on selenium (Preedy, 2015) and found that there is no additional relevant information which would modify the EFSA previous opinions. The FEEDAP Panel recently adopted an opinion on sodium selenite (coated granulated preparation) in the frame of re-evaluation (EFSA FEEDAP Panel, 2015).…”
Section: Additional Informationmentioning
confidence: 99%
“…Symptoms of deficiency and toxicosis of selenium in farm animals are described in detail in a previous opinions of the FEEDAP Panel (EFSA, 2006(EFSA, , 2011EFSA FEEDAP Panel, 2015) and scientific reviews (e.g. McDowell, 2003;Suttle, 2010).…”
Section: Safety For the Target Speciesmentioning
confidence: 99%
“…The FEEDAP Panel has already adopted two opinions on sodium selenite in the frame of re-evaluation (EFSA FEEDAP Panel, 2015, 2016.…”
Section: Additional Informationmentioning
confidence: 99%
“…3 Following the provisions of Article 10(1) of Regulation (EC) No 1831/2003, the compound was included in the EU Register of Feed Additives under the category "Nutritional additives" and the functional group "Compounds of trace elements". 4 The FEEDAP Panel has already adopted two opinions on sodium selenite in the frame of re-evaluation (EFSA FEEDAP Panel, 2015, 2016.…”
Section: Additional Informationmentioning
confidence: 99%